2023
DOI: 10.3390/d15030410
|View full text |Cite
|
Sign up to set email alerts
|

Exploring More on Dictyosporiaceae: The Species Geographical Distribution and Intriguing Novel Additions from Plant Litter

Abstract: Five fungal taxa collected from plant litter in Chiang Mai province, Thailand, are described with illustrations. The maximum likelihood, maximum parsimony, and Bayesian analyses of combined loci of the internal transcribed spacer (ITS), large subunit nuclear ribosomal DNA (LSU), and translation extension factor 1-α (tef1-α) region were used for phylogeny analyses. Dictyocheirospora acaciae is introduced as a new species from Acacia dealbata. Based on size differences in conidiomata, conidia, and DNA sequence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Within Dictyosporaceae, Dictyocheirospora and Dictyosporium are the two most prominent genera that accommodate the majority of freshwater species, with 11 and 9 reported freshwater species, respectively [24,25]. A geographical distribution review showed that numerous species within the family were reported from China and Thailand [2]. In this study, we describe an additional four hyphomycetes collected from freshwater habitats in China.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Within Dictyosporaceae, Dictyocheirospora and Dictyosporium are the two most prominent genera that accommodate the majority of freshwater species, with 11 and 9 reported freshwater species, respectively [24,25]. A geographical distribution review showed that numerous species within the family were reported from China and Thailand [2]. In this study, we describe an additional four hyphomycetes collected from freshwater habitats in China.…”
Section: Discussionmentioning
confidence: 92%
“…Dictyosporiaceae was established by Boonmee et al [1] to accommodate a group of cheiroid species, and it is classified within Pleosporales, Dothideomycetes. The species within Dictyosporiaceae exhibit the ability to colonize diverse decaying plant materials in both terrestrial and aquatic habitats, displaying a global distribution [2]. The introduction of novel genera has been significantly increased in the past two decades through extensive sampling and molecular phylogenetic analyses [1, [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sexual morph is scarcely known for this family, of which species of genera Dictyosporium , Gregarithecium , Immotthia , Pseudocoleophoma , Sajamaea and Verrucoccum have been represented as the sexual morph ( Boonmee et al 2016 ; Piątek et al 2020 ; Atienza et al 2021 ; Jiang et al 2021a ). Members of Dictyosporiaceae are morphologically diverse in various ecological niches, commonly known as saprobes on plant litter in terrestrial and freshwater habitats ( Tanaka et al 2015 ; Boonmee et al 2016 ; Li et al 2017 ; Crous et al 2019 ; Rajeshkumar et al 2021 ; Tian et al 2022 ; Tennakoon et al 2023 ). Besides, some genera were known as fungicolous (hyperparasites and mycoparasites) and lichenicolous fungi as well as inhabiting soil and herbivore dung ( Iturrieta-González et al 2018 ; Piątek et al 2020 ; Atienza et al 2021 ; Jiang et al 2021a ).…”
Section: Taxonomymentioning
confidence: 99%
“…An updated taxonomic description of Dictyosporiaceae was provided by Hongsanan et al (2020) who listed 15 genera in this family, while Wijayawardene et al (2022b) listed 17 genera in Dictyosporiaceae . Tennakoon et al (2023) provided a backbone tree of Dictyosporiaceae and currently listed 20 genera in this family, namely Aquadictyospora , Aquaticheirospora , Cheiro­sporium , Dendryphiella , Dictyocheirospora , Dictyopalmispora , Dictyo­sporium , Digito­desmium , Gregarithecium , Immotthia , Jalapriya , Neodendryphiella , Neodigito­desmium , Pseudocoleophoma , Pseudoconiothyrium , Pseudocyclo­thyriella , Pseudodictyosporium , Sajamaea , Verrucoccum and Vikalpa .…”
Section: Taxonomymentioning
confidence: 99%